“Diseño de un plan de mantenimiento productivo total (TPM) en la fábrica Todo Muebles para el mejoramiento de la productividad”. - Gualotuña Cabascango, Henry David (2021)
The present work will be developed in the Todo Muebles factory and its main focus is on improving productivity, each of these activities will be carried out through the elaboration of a total productive maintenance plan that seeks the optimal sustenance of the entire factory, good conservation of the equipment and correct application of tools that intervene in the process. In the first place, the analysis of equipment by levels was carried out using manuals and instructions to know the components of each equipment, concluding this procedure; identify the types, modes of failure that the machines can present and the preventive measures, elaborating in a logical sequence all the factors that intervene, such as; the coding of equipment, the calculation of criticality, definition of maintenance models, the technical sheet of each equipment, diagnosis and evaluation of faults, analysis of the maintenance plan through routes and inspections with their execution procedure and later the elaboration of the work orders. The preparation of the total productive maintenance plan seeks to train and involve the factory's operating personnel so that they know in detail their respective care and operation, through each of the proposed matrices so that it can be easily understood, quickly learned and fulfilled, thus obtaining strategies that benefit production, security, complementary activities, among others. The incorporation of this maintenance plan will benefit the reduction of the high rate of repetitive and repetitive failures, providing a high standard of reliability and availability, likewise the changes applied will be reflected with notoriety in the reduction of downtime, thus generating productivity. quality.